Inflorescence appearance timing and production rate traits in wild Zoysiagrass (Zoysia spp) - Han, Gyung Deok; Jung, Ji Hyeon; Chung, Yong Suk (Journal of Phytology, 2022)
Zoysiagrass (Zoysia spp.) has excellent turf quality and can be applied to various uses for personal space to public sports areas or commercial landscapes. However, it has disadvantages such as slow growth rate, cold hardiness, low seed yield, and hard to establish from seeds, which cannot be improved with agricultural practices. Therefore, breeding a new cultivar as a hybrid could be an efficient strategy to improve the Zoysiagrass cultivar. In fact, hybrid zoysiagrass shows mixed traits of both parents in morphology and heterosis in growth. However, inflorescence appearance and its rate are known to make a hybrid. Thus, the variety of inflorescence appearance timing and production rate were investigated among 549 genetic resources. As a result, only 5.38% of the variety among survived zoysiagrass after transplanting showed more than 30% inflorescence appearance within the given period. During that, some varieties showed a reduction of total inflorescence. Hence, we report the diversity of inflorescence appearance timing and production rate that could be useful for breeders and researchers breeding new Zoysiagrass cultivars.